2016
DOI: 10.1007/s11469-016-9661-7
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Dependence in Amateur Competitors and Non-Competitor Recreational Exercisers

Abstract: Research has demonstrated that exercising has health promoting effects. However, if habitual sporting activities become uncontrollable, detrimental health consequences can occur among a minority of individuals. Furthermore, such obligatory exercise can cause serious decline in school/work productivity, as well as financial problems, relationship problems, and poor psychological and physical wellbeing. The aim of the present study was to compare characteristics related to exercise dependence (ED) between recrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Participants were recruited from one semi-professional club for triathlon training and 17 different sports centers representative for Budapest (68,69). University students assisted with data collection, which resulted in 4,589 people signing the informed consent and they were all sent the study link.…”
Section: Exercisementioning
confidence: 99%
“…Participants were recruited from one semi-professional club for triathlon training and 17 different sports centers representative for Budapest (68,69). University students assisted with data collection, which resulted in 4,589 people signing the informed consent and they were all sent the study link.…”
Section: Exercisementioning
confidence: 99%
“…For example, Costa et al (2015) found the interaction between high levels of exercise identity and high social physique anxiety to contribute to 36% variation in exercise dependence symptoms in female competitive runners. Also, recent observational studies have found that exercise dependence symptoms are negatively correlated with self-esteem (e.g., Bruno et al, 2014;Menczel et al, 2017). Although this relationship is evident, future research is needed to determine the involvement of selfesteem in exercise dependence etiology.…”
Section: Psychological Theoriesmentioning
confidence: 99%
“…Individuals who are most susceptible to addiction are also at risk for exercise dependence. The exercise dependence literature indicates that individuals who are high in neuroticism (Hausenblas & Giacobbi, 2004), narcissism (Bruno et al, 2014), extraversion (Hausenblas & Giacobbi, 2004), and perfectionism (Costa, Coppolino, & Oliva, 2016;Hill, Robson, & Stamp, 2015;Lichtenstein, Christiansen, Elklit, Bilenberg, & Støving, 2014) and are low in agreeableness (Hausenblas & Giacobbi, 2004) and self-esteem (Bruno et al, 2014;Menczel et al, 2017) are more susceptible to developing exercise dependence than are those with the opposite levels of these traits. It is also likely that differences in brain structures and neurological agents contribute to the etiology of exercise dependence.…”
Section: Biological Theoriesmentioning
confidence: 99%
“…If the focus on exercise or the amount of exercise exceeds a certain level, the risk of physical overload and injury and/or psychological and social difficulties increase, as a result of great physiological and psychological demands on the individual, as well as conflicting time demands within other domains of daily life [ 1 , 4 , 30 ], Exactly how much exercise constitutes an excessive amount seems to vary between individuals, depending on the purpose of training [ 30 , 31 , 32 , 33 ], the individual’s age, their total stress in life [ 34 , 35 , 36 ], their gender [ 35 , 37 ], culture [ 38 , 39 ], exercise experience symptoms [ 40 ], and the context the activity is performed within [ 41 , 42 ]. Studies on larger populations have found that more than six hours’ weekly exercise increases the risk of exercise dependence [ 10 , 32 ], with a particular risk being associated with exercise levels above 10 to 12 h per week [ 8 , 36 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…As with both substance abuse [ 2 ] and eating disorders [ 10 ], people with low self-esteem are at higher risk of developing unhealthy motives for and addiction to exercise [ 51 ]. People who largely build their identity around being an athlete or exerciser, exercising more, and spending more time on exercise are also more vulnerable to developing an addiction to exercise [ 31 , 52 , 53 , 54 ]. In particular, this seems to be the case for those who experience low global self-esteem [ 55 ].…”
Section: Introductionmentioning
confidence: 99%